Approximate Implicitization Based on RBF Networks and MQ Quasi-Interpolation (Journal of Computational Mathematics, 2018)
In this paper, we propose a new approach to solve the approximate implicitization problem based on RBF networks and MQ quasi-interpolation. This approach possesses the advantages of shape preserving, better smoothness, good approximation behavior and relatively less data etc. Several numerical examples are provided to demonstrate the effectiveness and flexibility of the proposed method.
Keywords: RBF networks; MQ quasi-interpolation; Approximate implicitization; Rational curves.